Model of Magnetic Precession Gear Dynamics Based on 3D Finite Element Analysis and Prototype Investigation - Macyszyn, Łukasz; Jędryczka, Cezary; Mysiński, Michał (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
The presented research is focussed on analysis of dynamics of a two-stage magnetic precession gear system. In the proposed mathematical model of studied gear dynamics two approaches have been considered. Firstly, the model has been defined using the torque versus angle characteristics determined by means of detailed 3D FEM model of the magnetic field. In the second approach the model is based on torque vs. angle characteristics determined by measurements of the prototype step response. The results obtained by the two methods are compared and discussed.